Enhancement of quality small and cottage industries in Bangladesh: Review, analysis and strategies - Islam, Md. Ariful; Haque, A. F. M. Anwrul; Karim, A.N. Mustafizul (2002)
Small and cottage industries of a developing country like Bangladesh contribute significantly in national economy. These industries are producing various products and exporting them in different world markets along with the local markets. However, it becomes more difficult for them to maintain the quality level as per the requirements of the world market. In this context, management system has significant impact in producing quality product. Due to various limitations the small and cottage industries cannot maintain the expected quality in terms of product and production system. This research studies 50 small and cottage industries of Bangladesh as case studies to find out the existing conditions of them concerning quality level. Thereby it proposes some strategies to implement to enhance the overall quality of small and cottage industries.